Different factors are operative in shaping the epiphytic grapevine microbiome across different geographical scales: Biogeography, cultivar or vintage?. Issue 4 (13th September 2022) - Papadopoulou, Elena; Bekris, Fotios; Vasileiadis, Sotirios; Papadopoulou, Kalliope K.; Karpouzas, Dimitrios G.
Abstract: Introduction: The composition of the grapevine microbiome is controlled by a range of factors all contributing to the establishment of microbial terroir . Most studies have focused on the grape must microbiome, while less is known about the assemblage mechanisms of the epiphytic grapevine microbiome. We aimed to disentangle the role of geographic location, cultivar and vintage on the composition of the epiphytic fungal and bacterial communities of grapevine: within (regional scale) and across (national scale) viticultural zones in Greece. We hypothesised that: (i) the influence of all three factors varies at different geographical scales; (ii) fungi and bacteria respond differently to the factors shaping the grapevine microbiome. Materials and Methods: We analysed leaves and berries collected from Greek cultivars (i) Vidiano and Agiorgitiko located in three geographically distant regions (from 100 to >600 km), (ii) Roditis and Sideritis from different terroir units of the viticultural zone of Aigialeia. Results: Amplicon sequencing analysis identified strong regional signatures on the epiphytic microbiome across viticultural zones, whereas cultivar becomes a strong determinant at the viticultural zone scale. Fungal communities were more responsive to all studied factors compared to bacterial communities. Differential abundance (DA) analysis identified dominant fungal ( Alternaria, Cladosporium, Nigrospora, Aureobasidium, Vishniacozyma ) and bacterial ( Sphingomonas, Masillia, Streptococcus, Staphylococcus, Enterobacterales ) amplicon sequence variants (ASVs) exhibiting geographical and cultivar‐specific patterns. Conclusion: Our data suggest that different factors are operative in shaping the epiphytic grapevine microbiome at different geographical scales with bacterial and fungal communities showing different responses to the tested structural factors.